1953
DOI: 10.1161/01.cir.7.2.169
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hexamethonium on Certain Manifestations of Congestive Heart Failure

Abstract: Hypotensive doses of hexamethonium were administered intravenously to 19 patients with various types of heart disease in congestive failure. Clinical improvement as judged by the usual methods was seen in most cases. Intracardiac or pulmonary artery pressures paralleled the fall of arterial pressures following hexamethonium in four patients with hypertensive heart disease in congestive failure. It is suggested that hexamethonium, by reducing the total peripheral resistance and by a redistribution of blood volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1953
1953
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…However, the reason for the opposite effects of ouabain on the forearm vascular resistance and venous tone of the two groups of patients studied has not yet been completely elucidated.. Some investigators have postulated that the peripheral vasoconstriction in patients with congestive heart failure results from increased activity of the sympathetic nervous system (29), a view supported by the finding that the vasoconstriction has been diminished by ganglionic blockade (30,31). The elevation of cardiac output induced by ouabain in patients with heart failure may result in a diminution of the adrenergically induced arteriolar and venoconstriction in the forearm.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reason for the opposite effects of ouabain on the forearm vascular resistance and venous tone of the two groups of patients studied has not yet been completely elucidated.. Some investigators have postulated that the peripheral vasoconstriction in patients with congestive heart failure results from increased activity of the sympathetic nervous system (29), a view supported by the finding that the vasoconstriction has been diminished by ganglionic blockade (30,31). The elevation of cardiac output induced by ouabain in patients with heart failure may result in a diminution of the adrenergically induced arteriolar and venoconstriction in the forearm.…”
Section: Discussionmentioning
confidence: 99%
“…Hexamethonium by its blocking action on vasoconstrictor reflexes abolishes this increased tone thus permitting a decrease in total peripheral resistance and thereby also in the demand for cardiac work. These considerations and their implications in regard to the nature of congestive heart failure have been discussed more fully in another communication (20).…”
Section: Discussionmentioning
confidence: 99%
“…Reprinted with permission from Circulation. 9 Copyright American Heart Association, 1953.© The average fall in BP from the aorta to these small arteries was as follows: from aorta to 1-mm-diameter arteries, 7.5 mm Hg systolic and 5.5 mm Hg diastolic; and from aorta to 200-m-diameter arteries, 17 mm Hg systolic and 12 mm Hg diastolic. Therefore, the resistance vessels, where the steepest drop in BP occurs, must be in arterioles Ͻ200 m in diameter.…”
Section: Hemodynamics Of Blood Vessels Blood Pressure In Very Small Amentioning
confidence: 99%
“…Hexamethonium was the most effective, not only as an antihypertensive agent but also as a pharmacological tool in hemodynamic research. 9,11 Thiazide Diuretics I was fortunate to be the first to announce the treatment of hypertension with chlorothiazide at the 1957 annual meeting of the American Heart Association. 26 We found that chlorothiazide enhanced the antihypertensive action of other drugs more effectively than any other drug.…”
Section: Studies In Hypertension Early Drug Treatments Of Hypertensionmentioning
confidence: 99%